2009
DOI: 10.1021/nl803394v
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Single Crystalline Spinel LiMn2O4 Nanowires for a Lithium Ion Battery with High Power Density

Abstract: How to improve the specific power density of the rechargeable lithium ion battery has recently become one of the most attractive topics of both scientific and industrial interests. The spinel LiMn2O4 is the most promising candidate as a cathode material because of its low cost and nontoxicity compared with commercial LiCoO2. Moreover, nanostructured electrodes have been widely investigated to satisfy such industrial needs. However, the high-temperature sintering process, which is necessary for high-performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
345
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 505 publications
(360 citation statements)
references
References 34 publications
10
345
0
Order By: Relevance
“…20), synthesised by treating solvothermally prepared α-MnO2 nanowires with LiOH at reduced pressure, were single-crystalline in nature while their small diameter enabled accommodation of the large lattice parameter changes brought about by the cubic to tetragonal phase transitions. Larger diameter LiMn2O4 nanowires also showed good structural stability, maintaining their single-crystalline nature (as confirmed by selected area electron diffraction (SAED) analysis), even after 100 charge-discharge cycles [265]. Such results suggest that LiMn2O4 nanowires could represent the basis of potential high-power, high-rate Li-ion batteries.…”
Section: Limnxoymentioning
confidence: 68%
See 2 more Smart Citations
“…20), synthesised by treating solvothermally prepared α-MnO2 nanowires with LiOH at reduced pressure, were single-crystalline in nature while their small diameter enabled accommodation of the large lattice parameter changes brought about by the cubic to tetragonal phase transitions. Larger diameter LiMn2O4 nanowires also showed good structural stability, maintaining their single-crystalline nature (as confirmed by selected area electron diffraction (SAED) analysis), even after 100 charge-discharge cycles [265]. Such results suggest that LiMn2O4 nanowires could represent the basis of potential high-power, high-rate Li-ion batteries.…”
Section: Limnxoymentioning
confidence: 68%
“…Coupled with relatively low production costs and appreciable electrochemical performance at high discharge rates and elevated temperatures, LiMn2O4 is touted as a potential driver of future EV/HEV battery packs, notably against favourable LiFePO4 candidates [264]. Recent nanostructured morphologies of note include nanowires [265][266][267], nanorods [268][269][270][271][272], nanotubes [273], nanoparticles [269,[274][275][276] and ordered meso/porous electrodes [277,278]. Okubo et al [275] have demonstrated an important size-effect occurring in LiMn2O4 particles, confirming that bulk particle sizes are unable to achieve complete lithiation (up to Li2Mn2O4), due to their lower surface area.…”
Section: Limnxoymentioning
confidence: 99%
See 1 more Smart Citation
“…6 was fabricated by heating process after flux reaction of Na 0.44 MnO 2 nanowire as the template. 32) Generally, the fabrication of cubic crystal nanowire is difficult because the crystal structure is not anisotropy but isotropy. By using the self-template method, interesting materials were fabricated.…”
Section: Ion Batteries By Using Nanowires Materialsmentioning
confidence: 99%
“…However, today's conventional LIBs still suffer from rather slow charging/discharging performance using conventional electrode materials such as, for instance, graphite as a typical anode material [3]. Therefore, in recent years, huge efforts were made to increase the rate capabilities of LIB by introducing new electroactive material classes e.g., spinel-structured materials such as Li 4 Ti 5 O 12 (LTO) and LiMn 2 O 4 (LMO) in a wide range of accessible nanostructures such as nanoparticles [4][5][6], nanotubes [7][8][9], nanowires [10,11], nanosheets [12][13][14], mesoporous materials [15][16][17] and many more. Although increasing rate capabilities were successfully achieved, it is well known that the electrochemical properties of the electrode materials do not play the only key role, the electrode and current collector interface architecture [18,19] are key as well.…”
Section: Introductionmentioning
confidence: 99%